Pengaruh Komunikasi, Budaya Organisasi terhadap Gaya Kepemimpinan, Iklim Kerjasama dan Kepercayaan serta Komitmen Organisasi Dosen pada Perguruan Tinggi Swasta (Studi Harmonisasi Dosen Tetap Perguruan Tinggi Swasta di Kota Malang) - Susilo, Tri Achmad Budi; Rafid, Rahmad (LP3M Universitas Islam Zainul Hasan Genggong, 2022)
This study focuses on examining the extent to which communication, bureaucratic structure, and public support influence the performance of policy implementation related to the Tri Dharma of Higher Education. The findings indicate that communication, resources, bureaucratic structure, and public support significantly affect the implementation disposition. In particular, within the bureaucratic structure, public support has a notable impact on the core resources, namely lecturers or teaching staff. Furthermore, this study aims to analyze how communication and organizational culture influence leadership styles, the climate of collaboration and trust, as well as the organizational commitment of lecturers in private universities—especially in terms of harmonizing the implementation of the Tri Dharma. The research employs Structural Equation Modeling (SEM) to explore causal relationships among variables. A survey method was applied in this research, with a population consisting of lecturers from private universities in Malang, Indonesia. A total of 100 respondents from 11 private universities were selected as the research sample. The results show a direct and significant positive effect of organizational culture and communication on leadership styles, collaborative climate, trust, and organizational commitment among university lecturers. However, there is no significant direct effect of communication on organizational culture. Nonetheless, organizational communication significantly and positively influences both the collaborative climate and lecturers’ organizational commitment. Additionally, work-related trust also has a significant and positive impact on organizational commitment.